Versatile Grafting at the Nasal Tip - Koento, Trimartani (Facial Plastic Surgery, 2012)
Placing cartilage graft at the nasal tip is the most frequent technique to achieve proper tip projection and a well-balanced nose. The graft functions to support the nasal tip though reconstruction of the tripod concept legs and add greater definition to the tip. Tip grafts can be broadly classified into two categories: those that are used as mechanical nasal tip support, and those that are used for contouring or enchantment of nasal tip projection. This classification offers guidance to select the type of tip graft needed of overcome the present anatomy deformity.
Keywords: tip surgery; suturing technique; tip graft; open approach